PSYCHOLOGICAL PECULIARITIES OF DEVELOPMENT OF RESILIENCE AND CONSTRUCTIVE COPING STRATEGIES IN INTERNALLY DISPLACED PERSONS (Psychology Travelogs, 2025)
The article is devoted to the study of the problems of adaptation of internally displaced persons as a result of the full-scale war in Ukraine. The paper examines the main difficulties faced by IDPs, including economic, socio-psychological and institutional and legal aspects. Particular attention is paid to the need to develop constructive coping strategies and resilience as key factors for successful adaptation to the new socio-cultural environment. The article presents an analysis of current research on resilience as a personal quality that contributes to the transformation of stressors into such opportunities. The article presents the results of an interdisciplinary empirical study conducted on the basis of the Laboratory of Health Psychology of Bohdan Khmelnytsky Melitopol State Pedagogical University, which aimed to determine the level of resilience, dominant coping strategies and stress level among students - internally displaced persons. The results of the analysis of empirical research showed the dominance of non-constructive behavioral strategies, high levels of stress and low resilience among the average students surveyed. In order to improve the adaptive capacity of internally displaced persons, a psycho-correctional program based on the principles of rational-emotive therapy was developed and tested, which promoted the development of self-regulation skills, overcoming negative emotional states, expanding personal resources and included elements of augmented reality. The results of the study emphasize the importance of introducing innovative psychological technologies into the support system for internally displaced persons and the significance of the developed psychocorrectional programs in ensuring their successful adaptation to new living conditions. Prospects for further research are the analysis of modern approaches to the organization of systematic support for internally displaced persons, as well as the integration of the developed program into the system of comprehensive assistance at the initial stages of their adaptation to a new socio-cultural environment. We believe that the development of recommendations for professionals aimed at increasing the resilience, stress resistance, adaptability and social competence of internally displaced persons will also be relevant.
Keywords: internally displaced persons; resilience; coping strategies; stress; adaptation; psychological support; augmented reality